2017
DOI: 10.1155/2017/1851459
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Galla Chinensis Oral Solution as well as Its Stability, Safety, and Antidiarrheal Activity Evaluation

Abstract: Background of the Study As a widely used traditional medicine, Galla Chinensis is rich in tannins. However, there are few detailed studies about pharmaceutical preparations of Galla Chinensis tannin extract (GTE). In the present experiments, for better application and to investigate the possibility that Galla Chinensis tannin extract can be used as an antidiarrheal drug, we prepared Galla Chinensis oral solution (GOS). Materials and Methods GOS was prepared with GTE, and its physicochemical and microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…TA has been reported as a potential treatment for diarrhea in rats [31]. Moreover, Galla Chinensis extract (rich in TA) also played an anti-diarrhea role in castor oil and heat-labile enterotoxin (LT)-induced diarrhea models in mice [9,32]. Our experimental results showed that dietary supplementation of 0.2% or 1.0% TA significantly reduced the diarrhea rate of weaned piglets, which is consistent with previous research results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…TA has been reported as a potential treatment for diarrhea in rats [31]. Moreover, Galla Chinensis extract (rich in TA) also played an anti-diarrhea role in castor oil and heat-labile enterotoxin (LT)-induced diarrhea models in mice [9,32]. Our experimental results showed that dietary supplementation of 0.2% or 1.0% TA significantly reduced the diarrhea rate of weaned piglets, which is consistent with previous research results.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, some recent studies have shown that dietary TA has no effect or has some beneficial effect on the nutrient digestibility and growth performance of animals, which is contrary to the previous public cognition of TA [7,8]. In addition, many medicinal plants with effect on mitigating diarrhea have revealed the presence of TA, like Gallnut contains massive TA, which even can reach 50-70% of its weight [9]. Subsequently, the anti-diarrhea, anti-oxidation, microbial homeostasis regulation and other effects of TA have been found one after another, which have attracted extensive attention of animal nutritionists [4,10].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The extraction process of tannins and preparation of Galla chinensis oral solution (GOS) was described in our previous report [ 21 ]. Briefly, tannins from Galla chinensis were extracted by boiling water, and purified by removal of impurities through chloroform extraction and ethylacetate extraction, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, tannins extracted from Galla Chinensis were prepared as oral solution (GOS), which contained the tannins extract, purified water, appropriate sweeteners and antioxidant. We found that tannins extract showed significant antidiarrheal activity in a castor oil-induced diarrhea model in mice [ 21 ]. The acute toxicity study showed that the GOS is safe under the dose of 2500 mg/kg, and the LD 50 is 3247.47 mg/kg (Unpublished data).…”
Section: Introductionmentioning
confidence: 99%